Diagnostic relevance of 18F-FDG PET/CT in newly diagnosed patients with monoclonal gammopathy of undetermined significance (MGUS): Single-center experience - Sandecka, V; Adam, Z; Krejci, M; Stork, M; Rehak, Z; Koukalova, R; Sevcikova, S; Brozova, L; Kral, Z; Mayer, J; Pour, L (Neoplasma, 2020)
Monoclonal gammopathy of undetermined significance (MGUS) is a known precursor of more serious cancers, such as multiple myeloma (MM), Waldenström macroglobulinemia (MW) and other lymphoproliferative disorders. Using 18F-FDG PET/CT, we aimed to evaluate its benefit in early detection of various accompanying disorders and illnesses in MGUS patients. We prospectively analyzed the diagnostic relevance of 18F-FDG PET/CT in 390 newly diagnosed MGUS patients. On 18F-FDG PET/CT scans, the presence of focal or diffuse areas of detectable increased tracer uptake was recorded in 37 (9.5%) MGUS patients. The most frequent pathology was lymphadenopathy (3.8%), followed by thyroid diseases (2.1%), rheumatic diseases (1.8%), and other solid malignancies (1.5%). These results have major implications for confirmed associations of MGUS with numerous malignant and non-malignant disorders. We believe that 18F-FDG PET/CT imaging in newly diagnosed MGUS patients may be useful in early detection of other serious pathologies, not only in predicting progression of MGUS to active MM, and should be strongly recommended if available.
Keywords: dospělí; fluorodeoxyglukosa F18; monoklonální gamapatie nejasného významu; pozitronová emisní tomografie; lidé; Fluorodeoxyglucose F18; Multiple Myeloma; Monoclonal Gammopathy of Undetermined Significance; PET/CT; mnohočetný myelom; Positron Emission Tomography Computed Tomography; Adult; Positron-Emission Tomography; Humans